Pengaruh Transfer Pricing, Tunneling Incentive dan Profitabilitas terhadap Effective Tax Rate Rasio (ETR) - Safira, Meliana Ayu; Sodik, Sodik; Wahyudi, Untung (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study aims to examine the effect of transfer pricing, tunneling incentive and profitability on effective tax rate ratio both partially and simultaneously. This research is motivated by the occurance of several tax avoidance practices in several manufacturing companies in Indonesia. The population in this study amounted to 47 food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2019 period. Determination of the sample in this study using purposive sampling technique and obtained a sampel of 13 companies. The data analysis method used is multiple linier regression analysis using IBM SPSS software version 22. The results showed that the transfer pricing and profitability variables partially had a significant negative effect, while the tunneling incentive variable partially had an insignificant negative effect on the effective tax rate ratio. While simultaneously the three independent variables have a significant negative effect on the effective tax rate (ETR) ratio.